Evaluation of Quadruple Therapy (Pimobendan, Benazepril, Furosemide, Spironolactone) for the Treatment of Dilated Cardiomyopathy (DCM) in Dogs - Ashi.R.Krishna; K. Jeyaraja; R. Ramprabhu; S. Eswari; Mohamed Shafiuzama; S. Kavitha (The Indian Veterinary Journal, 2025)
Dilated cardiomyopathy is a common cardiac disease which affects larger breeds of dogs. The present study evaluated the occurrence of DCM in 10 dogs, its treatment and the treatment response. Ten dogs presented to the Medicine Outpatient unit of Madras Veterinary College Hospital presented with the clinical signs suggestive of DCM formed the study group. The animals were undergone general clinical examination, complete haematology, serum biochemistry, electrocardiography, thoracic radiography and echocardiography. Treatment was initiated with oral pimobendan, benazepril, diuretics and cardiac supportives. The cases showed substantial improvement after three months of treatment.